2011
DOI: 10.1161/circep.110.958744
|View full text |Cite
|
Sign up to set email alerts
|

MRI-Guided Ventricular Tachycardia Ablation

Abstract: Background-Substrate-guided ablation of ventricular tachycardia (VT)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 185 publications
(59 citation statements)
references
References 30 publications
2
57
0
Order By: Relevance
“…Our results are consistent with findings of contrast-enhanced CT to define the LV scar substrate. The area of first-pass hypoperfusion CT or late gadolinium-enhancement MRI approximated the area of less than 1.5 mV better than the area of less than 0.5 mV in patients with ischemic cardiomyopathy (13,17). All successful ablation sites were located within the SPECT-defined scar or within 1 cm of its border, with 73% of the successful ablation sites within 1 cm of the scar border.…”
Section: Correlations Of Myocardial Scar Area or Burden With Electropmentioning
confidence: 91%
See 1 more Smart Citation
“…Our results are consistent with findings of contrast-enhanced CT to define the LV scar substrate. The area of first-pass hypoperfusion CT or late gadolinium-enhancement MRI approximated the area of less than 1.5 mV better than the area of less than 0.5 mV in patients with ischemic cardiomyopathy (13,17). All successful ablation sites were located within the SPECT-defined scar or within 1 cm of its border, with 73% of the successful ablation sites within 1 cm of the scar border.…”
Section: Correlations Of Myocardial Scar Area or Burden With Electropmentioning
confidence: 91%
“…Correlating the possible exit location derived from the 12-lead morphology of the clinical or induced VT with the border of the SPECT scar model that has been integrated in the clinical mapping system may allow identification of an acceptable pace-map site without the performance of a full LV voltage map. Indeed, a similar approach using MRI scar models allowed the early identification of at least 11 of 12 pace-map sites in 64% of patients (17).…”
Section: Correlations Of Myocardial Scar Area or Burden With Electropmentioning
confidence: 99%
“…When integrated in the electroanatomic systems, it provides topography and transmural extent of the fibrotic tissue and, hence, of the low voltage areas, simplifying the identification of the arrhythmogenic substrate during voltage mapping in sinus rhythm [65,66] . This is expected to significantly shorten mapping time, increase the success rate and reduce the complication rate.…”
Section: Imaging Integrationmentioning
confidence: 99%
“…In general, ICD and claustrophobia are considered contraindications for magnetic resonance imaging. However, using appropriate precautions this imaging modality is possible even in ICD patients, who represent a vast proportion of candidates for VT ablation [38,66] .…”
Section: Imaging Integrationmentioning
confidence: 99%
“…Making the scar information from the MRI available within the ablation environment could help reduce procedure time. Dickfeld et al [11] have already showed the feasibility of 3D MRI scar reconstructions to facilitate VT ablations. The next step is the search for the best visual integration of the MRI scar information and the voltage measurements, which is the research topic described in this paper.…”
Section: Introductionmentioning
confidence: 99%